The impact of cranberry on lower urinary tract function: limitations due to gene expression and pharmacokinetic variability - Anisa VELEDAR-HAMALUKIĆ (Journal of Central European Agriculture)
Cranberries are well known for their antioxidative, anti-inflammatory, antimicrobial, and anti-biofilm formation properties. Many studies indicate their potential for cancer prevention, blood sugar regulation, gastrointestinal and cardiovascular health, and antiviral properties. Such wide therapeutic potential for human health has made cranberries favourable for dietary formulations. Considering how prone patients are to accept treatment via nature's pharmacy instead of the conventional one, cranberries in the form of juice, tablets, capsules, or extracts are often prescribed alongside antibiotic therapy for urinary tract infection (UTI) treatment. This review paper aims to provide a better understanding of the limitations of the usage of berry dietary formulations for health improvement. The healing potential of cranberries is limited due to the bioaccessibility of their ingredients and their pharmacokinetic properties. Although rich with pharmacologically active substances, including anthocyanins, proanthocyanidins, vitamin C, vitamins (B1, B2, B3, B5, B6, B9), and organic acids, their potential is limited due to low absorption and distribution, extensive metabolism, and elimination. The variability in gene expression affecting the biosynthesis of anthocyanins and proanthocyanidins within the Vaccinium berries results in diminished concentrations of active ingredients within the plant material itself. Also, the results from the clinical trials are inconsistently standardized. This paper offers a comprehensive analysis of the available data and presents a clear direction for future research.